Optimization of MAPbI3 Perovskite Solar Cell with Nano Structures - Hsieh, Yu-Chin; Huang, Jun-Yu; Wu, Yuh-Renn (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
Perovskite solar cell has been a promising low cost high efficiency solar cell and the efficiency increase rapidly. Since the crystal quality issues have been improved significantly, a further numerical optimization in the structure design is needed. We applied FDTD program for optical absorption and use our Poisson and drift-diffusion solver for electrical simulation. The Poisson and drift-diffusion solver is optimized for sovling organic and inorganic materials. Finally, we design a nano-structure that have efficiency of MAPBI 3 based solar cell has been improved from 18% to 19.67% That efficiency has be enhanced by 12% compared to the planar structure.